Insights From Dynamic Neuro-Immune Imaging on Murine Immune Responses to CNS Damage - Dorand, R. Dixon; Benson, Bryan L.; Huang, Lauren F.; Petrosiute, Agne; Huang, Alex Y. (Frontiers in Neuroscience, 2019)
Evolving technologies and increasing understanding of human physiology over the past century have afforded our ability to intervene on human diseases using implantable bio-materials. These bio-electronic devices present a unique challenge through the creation of an interface between the native tissue and implantable bio-materials: the generation of host immune response surrounding such devices. While recent developments in cancer immunology seek to stimulate the immune system against cancer, successful long-term application of implantable bio-material devices need to durably minimize reactive immune processes at involved anatomical sites. Peripheral immune system response has been studied extensively for implanted bio-materials at various body sites. Examples include tooth composites (Gitalis et al., 2019), inguinal hernia repair (Heymann et al., 2019), and cardiac stents and pacemaker leads (Slee et al., 2016). Studies have also been extended to less well-studied immune reactivity in response to CNS neural-electronic implant devices. Recent technological advances in 2-Photon Laser Scanning Microscopy (2P-LSM) have allowed novel insights into in vivo immune response in a variety of tissue microenvironments. While imaging of peripheral tissues has provided an abundance of data with regards to immune cell dynamics, central nervous system (CNS) imaging is comparatively complicated by tissue accessibility and manipulation. Despite these challenges, the results of dynamic intravital neuro-immune imaging thus far have provided foundational insights into basic CNS biology. Utilizing a combination of intravital and ex vivo 2P-LSM, we have observed novel pathways allowing immune cells, stromal cells, cancer cells and proteins to communicate between the CNS parenchyma and peripheral vasculature. Similar to what has been reported in the intestinal tract, we have visualized myeloid cells extend dendritic processes across the blood brain barrier (BBB) into pial blood vessels. Furthermore, transient vessel leaks seen during systemic inflammation provide opportunities for cellular protein to be exchanged between the periphery and CNS. These insights provide new, visual information regarding immune surveillance and antigen presentation within the CNS. Furthermore, when combining intravital 2P-LSM and microfluidic devices complexed with mathematical modeling, we are gaining new insights into the intravascular behavior of circulating immune cells. This new knowledge into the basic mechanisms by which cells migrate to and interact with the CNS provide important considerations for the design of neuro-electronic biomaterials that have the potential to connect the peripheral-neural microenvironments into a unique, artificial interface.